Atmospheric Research in Antarctica Present Status and Thrust Areas in Climate Change. - Khare, Neloy (Milton : CRC Press LLC, 2019)
Atmospheric Research in Antarctica: Present Status and Thrust Areas in Climate Change represents a panoramic view of the developments in the field of Antarctic atmospheric sciences and meteorology broadly covering geomagnetism and aeronomy, middle atmospheric studies and global and climate change studies. It includes greenhouse gases, ozone monitoring as well as very low frequency (VLF) phenomena, and space weather, Antarctic meteorology, and mathematical modeling of atmosphere and ocean processes around Antarctica. Atmospheric electricity and aerosols investigations over Antarctica along with the total solar eclipse-related studies, calibration of AWIFS Sensor, and measurements of positive ions, are also discussed. This book is aimed at researchers and graduate students in atmospheric studies, meteorology, Antarctic studies, climate change. FEATURES: Covers scientific aspects of Antarctic meteorology and atmospheric sciences under climate change scenario Contains diverse set of information with strong bearing on recent and past polar processes Presents integrated research on polar science coupled with meteorological, climatological and atmosphericsciences Thoroughly reviews geomagnetism and aeronomy, middle atmospheric studies including global and climate change studies Helps readers understand how Antarctica's climate has changed in the past and is being affected by global warming' and how might we expect its climate to change in the future?
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Environmental Engineering & Technology; Atmosphere -- Research -- Antarctica